Green Synthesis of Magnetite Nanoparticles (via Thermal Decomposition Method) with Controllable Size and Shape - Chin, S.F.; Pang, S.C.; Tan, Ching Hong (Journal of Materials and Environmental Science, 2011)
Magnetite (Fe3O4) nanoparticles with controllable size and shape were synthesized by the thermal decomposition method. In contrast to previously reported thermal decomposition methods, our synthesis method had utilized a much cheaper and less toxic iron precursor, iron acetylacetonate (Fe(acac)3), and environmentally benign and non-toxic polyethylene oxide (PEO) was being used as the solvent and surfactant simultaneously. Fe3O4 nanoparticles of controllable size and shape were prepared by manipulating the synthesis parameters such as precursor concentrations, reaction durations and surfactants.